State-of-the-art virtualisation technologies for the centralised automotive E/E architecture - Guo, Zixuan; Koufos, Konstantinos; Dianati, Mehrdad; Woodman, Roger (Frontiers in Future Transportation, 2025)
The automotive industry is undergoing profound changes, driven by the need for safer, more environmentally friendly, and more accessible future mobility and transport systems for goods and people. Enabling technologies include electrification, digitalisation, and automation of future vehicles. These technologies are powered by a multitude of onboard Electronic Control Units (ECUs). A typical modern vehicle has about 100 physical ECUs to enable various aspects of its function. These legacy many-ECU electronic/electrical (E/E) architecture models, known as distributed E/E architecture, are deemed inefficient as the number of ECUs and their processing power requirements keep increasing. In contrast, emerging centralised E/E architectures propose using fewer physical high-performance onboard processors on which an almost unlimited number of virtual ECUs can be created to handle various legacy and modern applications. As a result, virtualisation techniques, which enable multiple virtual ECUs with different operating systems to run concurrently on a single hardware platform, are promising models for modern centralised E/E architectures. Motivated by this trend, this paper provides a structured and comprehensive state-of-the-art review of virtualisation techniques for automotive applications, covering areas such as resource allocation, AUTOSAR, peripheral I/O interfaces, and in-vehicle communication networks. We comprehensively review the literature and identify research gaps in virtualisation techniques for cache management, paravirtualsation, software-defined networking for in-vehicle networks, and virtualisation for enhanced prototyping and testing in the context of modern E/E architectures for modern vehicles.